1984
DOI: 10.1002/bjs.1800710324
|View full text |Cite
|
Sign up to set email alerts
|

The urgent diagnosis of gallstones in acute pancreatitis: A prospective study of three methods

Abstract: Ultrasonography (US), radionuclide biliary scanning (RBS), and biochemical tests were performed within 72 h of admission in 83 patients with acute pancreatitis in an attempt to define those with gallstones as an aetiological factor. US was 92 per cent accurate in the 80 per cent of patients in whom the gallbladder was demonstrated. There were no false positives. Sixty-seven per cent of patients with gallstones were diagnosed although this improved to 78 per cent when US was repeated following the patients' cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
2
2

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(47 citation statements)
references
References 24 publications
3
40
2
2
Order By: Relevance
“…5,18 In our series, ultrasonography confirmed the biliary cause of the disease in all but one patient. In addition, ultrasonography is an inexpensive technique, readily available, and noninvasive, and therefore it can be used repeatedly to monitor the evolution of the disease.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…5,18 In our series, ultrasonography confirmed the biliary cause of the disease in all but one patient. In addition, ultrasonography is an inexpensive technique, readily available, and noninvasive, and therefore it can be used repeatedly to monitor the evolution of the disease.…”
Section: Discussionsupporting
confidence: 69%
“…19 Studies reported that the sensitivity of ultrasonography in detecting bile duct stones is limited in patients with acute pancreatitis because of the tympanites and ileus related to this clinical condition. 2,18,20,21 In our study ultrasonography showed lithiasis or sludge of the common bile duct in a higher percentage of patients with acute pancreatitis than that reported in the literature. Because ultrasonography is highly operator-dependent, the high percentage of patients with acute pancreatitis in whom this technique demonstrated lithiasis or sludge of the common bile duct may be partly due to the experience of the sonographer or to a more careful examination of the common bile duct.…”
Section: Discussionsupporting
confidence: 49%
“…In Nepal, the exact data are unavailable, but one study has suggested it to be as common as alcoholic pancreatitis, together accounting for about 66 % of all causes [6]. The diagnosis of gallstone (biliary) pancreatitis can be made by ultrasonography and by liver enzymes [7,8]. The sensitivity of the ultrasonography in the detection of gallstones is more than 95 % in uncomplicated cases, but this reduces to 67-78 % during an attack of pancreatitis due to the ileus [7].…”
Section: Introductionmentioning
confidence: 99%
“…It has several advantages as compared to contrast-enhanced computed tomography (CT) and magnetic resonance imaging (MRI), such as low cost, real time evaluation and no radiation exposure. 49 US can be performed easily at patient's bedside and demonstrates good values of sensitivity and specificity in the assessment of AP (67 and 100%, respectively). 50 Furthermore, US is useful in the follow-up of the patients, revealing local complications such as abscesses, necrosis, peripancreatic fluid, pseudocysts, abscesses and vascular disease (venous thrombosis and pseudoaneurysms).…”
Section: Role Of Ultrasound In Acute Pancreatitismentioning
confidence: 99%